Hazara orthonairovirus nucleoprotein facilitates viral cell-to-cell spread by modulating tight junction protein, claudin-1 - Ohta, Keisuke; Saka, Naoki; Fukasawa, Masayoshi; Nishio, Machiko (Frontiers in Microbiology, 2023)
Background: Tight junctions act as a barrier that prevents invasion of pathogens through epithelial cells. This study aims to elucidate the correlation between tight junctions and nairoviruses using Hazara orthonairovirus (HAZV) as a surrogate model for Crimean-Congo hemorrhagic fever virus. Methods: mRNA, total protein, and cell surface protein levels of tight junction proteins were examined by quantitative real-time reverse transcription polymerase chain reaction, immunoblot and flow cytometry, respectively. HAZV growth was measured by plaque assay. Immunofluorescence assay was used to examine viral cell-to-cell spread. The interaction between HAZV nucleoprotein and claudin-1 was analyzed by immunoprecipitation. Results: HAZV infection induced mRNA of several tight junction proteins, especially claudin-1. HAZV infection also induced cell surface expression of claudin-1 protein. Claudin-1 overexpression inhibited the growth of HAZV by blocking its cell-to-cell spread. In contrast, HAZV nucleoprotein completely inhibited HAZV-induced cell surface expression of claudin-1, and this inhibition required interaction between HAZV nucleoprotein and claudin-1. Conclusion: HAZV nucleoprotein was shown to bind to claudin-1 to negatively regulate its cell surface expression, and so can promote cell-to-cell spread of HAZV. This is the first presentation of a possible mechanism behind how nairoviruses counteract tight junction barrier function.